The emotional impact of videogames and poetry. - Sánchez Trigo, Clara (My University, 2023)
When we are moved by a story, what affected us so? My doctoral project explores this question to better understand how stories convey emotion and move its audience. Inspired by the renewed scholarly interest in emotions and affect, I wish to look into the relationship between the work, the receiver and authorial intention with a focus on feelings. Rita Felski has recently explored the bond between reader and work in terms of attachment and identification in Hooked: Art and Attachment (2020), and emphasizes that not only content, but also aesthetic devices and personal experience play a significant role. I approach the emotional relationship between artwork and receiver by comparing two media—poetry and videogames—that allow for narrative storytelling while each offering very different affordances. I wish to analyse what features make the works in my corpus moving and which of them are specific to each medium or, if any, common to both poetry and videogames. I use affect theory, especially regarding the concepts of identification, by Felski (2020) and resonance by Massumi (1995), to analyse emotivity in my corpus. My preliminary corpus finds unity both in the time period, as it comprises works released in the last ten to fifteen years, and in its topic, as the works in my preliminary selection all revolve around families, memory and intergenerational relationships and trauma. With these elements in common, I try to elucidate what sets them apart in affective terms. The videogames selected so far are all narrative-driven games, namely, What Remains of Edith Finch (2017), Gone Home (2013), and The Suicide of Rachel Foster (2020). The poetry works include the collections by Rupi Kaur but other poets are still to be determined.
Keywords: Estética de la recepción; Poesía - Aspectos psicológicos; Videojuegos - Aspectos psicológicos; Narrative videogame; Affect; Resonance; Identification; Poetry